Perencanaan Kapasitas dan Waktu Produksi Tahu di Rumah Produksi Bapak Rahim, Sentra Industri Kecil Somber Balikpapan - Aditya Permana; Endrawati, Budiani Fitria; Pratikno, Faishal Arham (LPPM ITK, 2023)
The Somber Small Industry Center's Regional Technical Implementation Unit (UPTD) is one of Balikpapan's tofu and tempeh industrial sectors. Based on observations performed throughout the implementation of tofu production at Mr. Rahim's production house, it is known that the production capacity of tofu varies every month due to the shortage of a tofu production plan, resulting in Mr. Rahim's production house losing 816 kg worth Rp. 20.400.000 in 2022. The purpose of this study was to plan and offer recommendations for tofu manufacturing capacity and time that are suitable for Mr. Rahim's production house. Forecasting moving averages, weight moving averages, exponential smoothing, and linear trend line models are applied in the tofu production planning approach. The research results in capacity planning and production time of tofu using the forecasting method of moving average over 3 periods and 6 periods, respectively, 6081 kg/month and 6025 kg/month; weight moving average over 3 periods and 2 periods, respectively, 5792 kg/month and 5504 kg/month; exponential smoothing method with alpha 0.80, 0.90, and 0.95, respectively, 5258 kg/month, 5080 kg/month, and 4990 kg/month; and the linear trend line model method of 6317 kg/month. The conclusion of this study using the best feasible forecasting method is the weight moving average with two weighting periods, with a total required capacity of tofu production time of 1671.0144 hours/year and a total capacity of available tofu production time of 1874.6112 hours/year due to the difference in actual demand with a forecast of 732 kg, which does not exceed the value of lost sales in 2022.